Policy and the Impact on Placement, Involvement, and Progress in General Education: Critical Issues That Require Rectification. (March 2014) - Ryndak, Diane Lea; Taub, Debbie; Jorgensen, Cheryl M.; Gonsier-Gerdin, Jean; Arndt, Katrina; Sauer, Janet; Ruppar, Andrea L.; Morningstar, Mary E.; Allcock, Heather
Students with significant disabilities continue to be among the most segregated in schools. In this article, we argue that the principles of least restrictive environment and involvement and progress in the general curriculum have been interpreted in ways that perpetuate segregation, rather than increasing students' access to meaningful curriculum in inclusive educational contexts. We examine this issue from three broad perspectives: federal policy related to least restrictive environment, interpretations of policies related to involvement and progress in the general curriculum, and the implementation of policies related to assessment of grade-level standards. We discuss implications of each of these issues for providing and increasing involvement and progress in general education contexts and content.